Effects of deworming on child and maternal health: a literature review and meta-analysis - Winter Maxwell Thayer; Adrienne Clermont; Neff Walker (BMC Public Health, 2017)
Abstract Background Soil-transmitted helminth infections are widespread. Many studies have been published on the topic of deworming. The Lives Saved Tool (LiST) is a software package that uses a deterministic mathematical model to estimate the effect of scaling up interventions on maternal and child health outcomes. This review investigates the scope of available evidence for benefits of deworming treatments in order to inform a decision about possible inclusion of deworming as an intervention in LiST. Methods We searched PubMed, the Cochrane Library, and Google Scholar. We included studies that reported pre/post data in children younger than 5 years or pregnant women for outcomes related to mortality and growth. We excluded studies that compared different anthelminthic treatments but did not include a placebo or non-treatment group, and those that did not report post-intervention outcomes. We categorized articles by treated population (children younger than 5 years and pregnant women), experimental versus observational, mass drug administration (MDA) versus treatment, and reported outcome. Results We identified 58 relevant trials; 27 investigated children younger than 5 years and 11 investigated pregnant women; one reported on both children younger than 5 years and pregnant women. We conducted meta-analyses of relevant outcomes in children younger than 5 years. Conclusions Deworming did not show consistent benefits for indicators of mortality, anemia, or growth in children younger than five or women of reproductive age. We do not recommend including the effect of deworming in the LiST model.